PAKISTAN’S ROLE IN THE RISE OF RELIGIOUS RADICALISM IN AFGHANISTAN - Ikrom Khudayberdiyev (Western European Studies, 2025)
As we know, Islamic radicalism in Central Asia has become part of the process of globalization. Without knowing its deep roots and foundations, it is very difficult to understand how this situation arose. The main purpose of the article is to analyze the influence of international forces, external relations and relationships in the evolution and emergence of Islamic radicalism in Central Asia, despite their remote location. If we consider the historical aspects of Islamic radicalism in connection with the events of September 11, 2001, we can see the emergence of Pakistani Islamic radicalism and Afghan jihad
Keywords: militarization of Islam; Saur Revolution; mujahideen